Kraken : the curious, exciting, and slightly disturbing science of squid / by Wendy Williams. - Williams, Wendy, 1950- (Abrams Image, 2011)
In addition to squid, both giant and otherwise, Kraken examines other cephalopods, including the octopus and cuttlefish.